Effectiveness of women in managerial roles in the corporate sector in India - Nayak, Parameshwar (Teorija in praksa, 2018)
This article seeks to understand how female managers in public- and private-sector companies in India are perceived by their colleagues in terms of managerial effectiveness. It is based on a primary research study using a structured questionnaire to collect data from 1,260 managers of 60 companies in India and indepth-interviews with 30 senior corporate executives. The majority of them think gender does impact managerial effectiveness. While the competencies of managers are considered to be the key determining factor of their effectiveness at work, men are preferred for certain vital roles such as top leadership, strategic decision-making, negotiation, handling risks and challenges. However, women are regarded as more effective in human resources, public relations, inter-personal relations and maintaining work-life balance.
Keywords: Effectiveness; Leadership; Managerji; Managers; Učinkovitost; Vodenje; Women; Ženske